O fazer artístico de Escurinho sob perspectiva etnomusicológica - Linhares, Maria Juliana Figueredo (2015)
Research on the artistic career of the composer, percussionist and singer Jonas Epifânio dos Santos Neto, known as Escurinho present in the urban music scene in João Pessoa since the late 1980s. To interpret how to weave the threads of popular music during the life of a performer, the theoretical and methodological bases of ethnomusicology (BLACKING, 1995 MUKUNA, 2008, MERRIAM, 1980) dialogue with the bases of the interpretive anthropology (GEERTZ, 2008), history of life (CHIZZOTTI, 2006), the sociological "structuralist constructivism" (BOURDIEU, 1996), philosophy (BAKHTIN, 2006), and visual anthropology (HARTMANN, 2001). The work seeks to understand the history of life, not just as an individual artistic saga, but as a reflection of the trends of urban social movements in local and global level. The results it’s a tour by the music scene of the city of João Pessoa, through Escurinho reports, and the analysis of his work.